IDENTIFIKASI DAN INTEPRETASI AGROKLIMAT MOJOSARI, JAWA TIMUR - Yanto Sugianto; Bisman Nababan; Darmijati S.; H. Syahbuddin; Irsal Las (PERHIMPI (Indonesian Association of Agricultural Meteorology), 1993)
Abstract is available in the full text (pdf format)